Functional-State Dependence of Picosecond Protein Dynamics - George, D. K.; Chen, J. Y.; He, Yunfen; Knab, J. R.; Markelz, A. G. (J. Phys. Chem. B, 2021)
We examine temperature-dependent picosecond dynamics of two benchmarking proteins lysozyme and cytochrome c using temperature-dependent terahertz permittivity measurements. We find that a double Arrhenius temperature dependence with activation energies E1 ∼ 0.1 kJ/mol and E2 ∼ 10 kJ/mol fits the folded and ligand-free state response. The higher activation energy is consistent with the so-called protein dynamical transition associated with beta relaxations at the solvent–protein interface. The lower activation energy is consistent with correlated structural motions. When the structure is removed by denaturing, the lower-activation-energy process is no longer present. Additionally, the lower-activation-energy process is diminished with ligand binding but not for changes in the internal oxidation state. We suggest that the lower-energy activation process is associated with collective structural motions that are no longer accessible with denaturing or binding.

The 2017 terahertz science and technology roadmap - Dhillon, S. S.; Vitiello, M. S.; Linfield, E. H.; Davies, A. G.; Hoffmann, M. C.; Booske, J.; Paoloni, C.; Gensch, M.; Weightman, P.; Williams, G. P.; Castro-Camus, E.; Cumming, D. R. S.; et al. (Journal of Physics D-Applied Physics, 2017)
Science and technologies based on terahertz frequency electromagnetic radiation (100 GHz-30 THz) have developed rapidly over the last 30 years. For most of the 20th Century, terahertz radiation, then referred to as sub-millimeter wave or far-infrared radiation, was mainly utilized by astronomers and some spectroscopists. Following the development of laser based terahertz time-domain spectroscopy in the 1980s and 1990s the field of THz science and technology expanded rapidly, to the extent that it now touches many areas from fundamental science to 'real world' applications. For example THz radiation is being used to optimize materials for new solar cells, and may also be a key technology for the next generation of airport security scanners. While the field was emerging it was possible to keep track of all new developments, however now the field has grown so much that it is increasingly difficult to follow the diverse range of new discoveries and applications that are appearing. At this point in time, when the field of THz science and technology is moving from an emerging to a more established and interdisciplinary field, it is apt to present a roadmap to help identify the breadth and future directions of the field. The aim of this roadmap is to present a snapshot of the present state of THz science and technology in 2017, and provide an opinion on the challenges and opportunities that the future holds. To be able to achieve this aim, we have invited a group of international experts to write 18 sections that cover most of the key areas of THz science and technology. We hope that The 2017 Roadmap on THz science and technology will prove to be a useful resource by providing a wide ranging introduction to the capabilities of THz radiation for those outside or just entering the field as well as providing perspective and breadth for those who are well established. We also feel that this review should serve as a useful guide for government and funding agencies.
Keywords: ex-vivo; generation; metal wave-guides; near-field; performance; photoconductive emitters; Physics; quantum-cascade lasers; radiation; semiconductors; Terahertz; thz; time-domain spectroscopy

Photoactive yellow protein terahertz response: hydration, heating and intermediate states - George, Deepu K; Knab, Joseph R; He, Yunfen; Kumauchi, Masato; Birge, Robert R; Hoff, Wouter D; Markelz, Andrea G (IEEE Transactions on Terahertz Science and Technology, 2013)

Functional State Dependence of Picosecond Protein Dynamics - Chen, J. Y.; George, D. K.; He, Y.; Knab, J. R.; Markelz, A.G. (arXiv:1105.4425, 2012)

Evidence of protein collective motions on the picosecond timescale - He, Yunfen; Chen, J-Y; Knab, Joseph R; Zheng, Wenjun; Markelz, Andrea G (Biophysical Journal, 2011)

Why is THz Sensitive to Protein Functional States? Oxidation State of Cytochrome C - He,Y.; Chen, J.-Y.; Knab, J. R.; Zheng, W.; Markelz, A.G. (Terahertz Science and Technology, 2010)
We investigate the presence of structural collective motions on a picosecond time scale for the heme protein, cytochrome c, as a function of oxidation and hydration, using terahertz (THz) time-domain spectroscopy and molecular dynamics simulations. Structural collective mode frequencies have been calculated to lie in this frequency range, and the density of states can be considered a measure of flexibility. A dramatic increase in the THz response occurs with oxidation, with the largest increase for lowest hydrations and highest frequencies. For both oxidation states the measured THz response rapidly increases with hydration saturating above ~25% (g H2O/g protein), in contrast to the rapid turn-on in dynamics observed at this hydration level for other proteins. Quasi-harmonic collective vibrational modes and dipole-dipole correlation functions are calculated from the molecular dynamics trajectories. The collective mode density of states alone reproduces the measured hydration dependence providing strong evidence of the existence of these collective motions. The large oxidation dependence is reproduced only by the dipole-dipole correlation function, indicating the contrast arises from diffusive motions consistent with structural changes occurring in the vicinity of a buried internal water molecule.

The role of the protein surface on the local biological water dynamics - Liang, W.; He, Y. F.; George, D.; Markelz, A. G. (Biosensing Ii, 2009)
Protein function is reliant on structural flexibility and this flexibility is slaved to the surrounding solvent. Here we discuss how the exposed surface of the protein influences the solvent dynamics and thereby influences the protein's own structural dynamics. We discuss measurements of the THz absorption of water in the presence of hydrophilic and hydrophobic surfaces.
Keywords: alanine; dynamics; hydration; lysine; lysozyme; proteins; relaxation; spectroscopy; Terahertz; thz

The role of structure in the protein dynamical transition - He, Yunfen; Markelz, Andrea G (2008 33rd International Conference on Infrared, Millimeter and Terahertz Waves, 2008)

Development of Tagless Biosensors for Detecting the Presence of Pathogens - Markelz, A. G.; Chen, J.-Y.; Knab, J. R.; He, Y.; Ye, S. (Terahertz Frequency Detection and Identification of Materials and Objects, 2007)

Protein dynamical transition in terahertz dielectric response - Markelz, Andrea G.; Knab, Joseph R.; Chen, Jing Yin; He, Yunfen (Chemical Physics Letters, 2007)
The 200K protein dynamical transition is observed for the first time in the terahertz dielectric response. The complex dielectric permittivity ε=ε′+iε″ is determined in the 0.2–2.0THz and 80–294K ranges. ε″ has a linear temperature dependence up to 200K then sharply increases. The low temperature linear dependence in ε″ suggests anharmonicity for temperatures 80K<t<180k, challenging="" the="" assumed="" harmonicity="" below="" 200k.="" temperature="" dependence="" is="" consistent="" with="" thermally="" activated="" sidechain="" motions="" and="" shows="" involved="" in="" dynamical="" transition="" extend="" to="" subpicosecond="" time="" scales.<="" div="">

Terahertz dielectric assay of solution phase protein binding - Chen, J. Y.; Knab, J. R.; Ye, S. J.; He, Y. F.; Markelz, A. G. (Applied Physics Letters, 2007)
The authors demonstrate a method for rapid determination of protein-ligand binding on solution phase samples using terahertz dielectric spectroscopy. Measurements were performed using terahertz time domain spectroscopy on aqueous solutions below the liquid-solid transition for water. Small ligand binding sensitivity was demonstrated using triacetylglucosamine and hen egg white lysozyme with a decrease in dielectric response with binding. The magnitude of the change increases with frequency. (c) 2007 American Institute of Physics.
Keywords: dynamics; lysozyme; Physics; spectroscopy; water

Terahertz measurements of protein relaxational dynamics - Knab, Joseph R; Chen, Jing-Yin; He, Yunfen; Markelz, Andrea G (Proceedings of the IEEE, 2007)

Protein conformational dynamics measured with terahertz time domain spectroscopy - Knab, Joseph R; Chen, Jing-Yin; Ye, Shuji; He, Yunfen; Markelz, Andrea G (2006 Joint 31st International Conference on Infrared Millimeter Waves and 14th International Conference on Teraherz Electronics, 2006)

Using terahertz spectroscopy as a protein binding assay - Chen, J.-Y.; Knab, J. R.; Ye, S.; He, Y.; Markelz, A. G. (Advanced Biomedical and Clinical Diagnostic Systems IV, 2006)
The vibrational modes corresponding to protein tertiary structural motion lay in the far infrared or terahertz frequency range. These collective large scale motions depend on global structure and thus will necessarily be perturbed by ligand binding events. We discuss the use of terahertz dielectric spectroscopy to measure these vibrational modes and the sensitivity of the technique to changes in protein conformation, oxidation state and environment. A challenge of applying this sensitivity as a spectroscopic assay for ligand binding is the sensitivity of the technique to both bulk water and water bound to the protein. This sensitivity can entirely obscure the signal from the protein or protein-ligand complex itself, thus necessitating sophisticated sample preparation making the technique impractical for industrial applications. We discuss methods to overcome this background and demonstrate how terahertz spectroscopy can be used to quickly assay protein binding for proteomics and pharmaceutical research.

Terahertz measurements of the Photoactive Protein Bacteriorhodopsin mutant D96N: M and P states - Chen, C.-Y.; Knab, J. R.; Cerne, J.; Hillebrecht, J. R.; Birge, R. R.; Markelz, A. G. (Mater. Res. Soc. Symp., 2004)
We use terahertz (THz) spectroscopy as a biomaterials characterization tool. Previously we have shown a strong contrast between the THz dielectric response for wild type (WT) and D96N mutant of bacteriorhodopsin. In those studies we observed a large increase in the THz absorbance of WT with excitation to thermally captured photo-intermediates whereas no such increase in absorbance was observed for the mutant D96N. These results suggest that the THz response is sensitive to structural changes and relative flexibility of biomolecules. However the photo-intermediate populations of the WT and D96N samples were not equivalent in those measurements. While the WT samples had relaxed (bR), M and P state intermediates present, the D96N samples had only bR and M states. Here we present terahertz absorbance measurements of D96N as a function of M and P state populations at room temperature. The THz response is constant for intermediate states populations up to 23% M state and up to 30% P state. These results verify that there is a fundamental difference in the conformational dynamics as measured by THz dielectric response for a single residue mutation.

Protein flexibility and conformational state: A comparison of collective vibrational modes of wild-type and D96N bacteriorhodopsin - Whitmire, S. E.; Wolpert, D.; Markelz, A. G.; Hillebrecht, J. R.; Galan, J.; Birge, R. R. (Biophysical Journal, 2003)
Far infrared ( FIR) spectral measurements of wild-type (WT) and D96N mutant bacteriorhodopsin thin films have been carried out using terahertz time domain spectroscopy as a function of hydration, temperature, and conformational state. The results are compared to calculated spectra generated via normal mode analyses using CHARMM. We find that the FIR absorbance is slowly increasing with frequency and without strong narrow features over the range of 2-60 cm(-1) and up to a resolution of 0.17 cm(-1). The broad absorption shifts in frequency with decreasing temperature as expected with a strongly anharmonic potential and in agreement with neutron inelastic scattering results. Decreasing hydration shifts the absorption to higher frequencies, possibly resulting from decreased coupling mediated by the interior water molecules. Ground-state FIR absorbances have nearly identical frequency dependence, with the mutant having less optical density than the WT. In the M state, the FIR absorbance of the WT increases whereas there is no change for D96N. These results represent the first measurement of FIR absorbance change as a function of conformational state.
Keywords: angstrom resolution; Biophysics; dna; films; frequency; harmonic-analysis; inelastic neutron-scattering; large systems; mixed basis; normal-modes; purple membranes; structural-changes; transform infrared-spectroscopy

Ultrafast THz spectroscopy of photoactive biomolecules - Chen, J.-Y.; Whitmire, S. E.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Ultrafast Phenomena in Semiconductors VII, 2003)

THz time domain spectroscopy of biomolecular conformational modes - Markelz, Andrea; Whitmire, Scott; Hillebrecht, Jay; Birge, Robert (Physics in Medicine & Biology, 2002)

Terahertz Time domain spectroscopy of the M intermediate state of Bacteriorhodopsin - Whitmire, S.; Markelz, A. G.; Hillebrecht, J. R.; Birge, R. R. (Proceedings of the 26th International Conference on Infrared and Millimeter Waves, 2001)

Pulsed terahertz spectroscopy of DNA, bovine serum albumin and collagen between 0.1 and 2.0 THz - Markelz, A. G.; Roitberg, A.; Heilweil, E. J. (Chemical Physics Letters, 2000)
We report the first use of pulsed terahertz spectroscopy to examine low-frequency collective vibrational modes of biomolecules. Broadband absorption increasing with frequency was observed for lyophilized powder samples of calf thymus DNA, bovine serum albumin and collagen in the 0.06-2.00 THz (2-67 cm(-1)) frequency range, suggesting that a large number of the low-frequency collective modes for these systems are IR active. Transmission measurements at room temperature showed increasing FIR absorption with hydration and denaturing. (C) 2000 published by Elsevier Science B.V. All rights reserved.
Keywords: b-dna; Chemistry; films; modes; Physics; proteins

Temperature-dependent terahertz output from semi-insulating GaAs photoconductive switches - Markelz, A. G.; Heilweil, E. J. (Applied Physics Letters, 1998)
The temperature dependence of the terahertz (THz) output power and spectra from biased photoconductive switches was measured for several antenna gap widths and applied biases. The spectrally integrated THz output had a nonmonotonic temperature dependence in all cases with the value increasing by a factor of 3 from room temperature to 150 K for low biases and 100 K at high biases. An abrupt decrease in output power occurs below 90 K, and the spectrum shifts to lower frequencies as the temperature is lowered. (C) 1998 American Institute of Physics.
Keywords: domain; generation; Physics; pulses; semiconductor surfaces; transmission spectroscopy

Undressing a collective intersubband excitation in a quantum well - Craig, K.; Galdrikian, B.; Heyman, J. N.; Markelz, A. G.; Williams, J. B.; Sherwin, M. S.; Campman, K.; Hopkins, P. F.; Gossard, A. C. (Physical Review Letters, 1996)
We have experimentally measured the 1-2 intersubband absorption in a single 40 nm wide modulation-doped Al0.3Ga0.7As/GaAs square quantum well as a function of frequency, intensity, and charge density. The low-intensity depolarization-shifted absorption occurs near 80 cm(-1) (10 meV or 2.4 THz), nearly 30% higher than the intersubband spacing. At higher intensities, the absorption peak shifts to lower frequencies. Our data are in good agreement with a theory proposed by Zaluzny, which attributes the redshift to a reduction in the depolarization shift as the excited subband becomes populated.

NONLINEAR QUANTUM DYNAMICS IN SEMICONDUCTOR QUANTUM-WELLS - Sherwin, M. S.; Craig, K.; Galdrikian, B.; Heyman, J.; Markelz, A.; Campman, K.; Fafard, S.; Hopkins, P. F.; Gossard, A. (Physica D-Nonlinear Phenomena, 1995)
We discuss recent measurements of the nonlinear response of electrons in wide quantum wells driven by intense electromagnetic radiation at terahertz frequencies. The theme is the interplay of quantum mechanics, strong periodic driving, the electron-electron interaction and dissipation. We discuss harmonic generation from an asymmetric double quantum well in which the effects of dynamic screening are important. Measurements and theory are found to be in good agreement. We also discuss intensity-dependent absorption in a 400 Angstrom square quantum well. A new nonlinear quantum effect occurs, in which the frequency at which electromagnetic radiation is absorbed shifts to the red with increasing intensity. The preliminary experimental results are in agreement with a theory by Zaluzny, in which the source of the nonlinearity is the self-consistent potential in the Hartree approximation for the electron dynamics.

RESONANT-ENERGY RELAXATION OF TERAHERTZ-DRIVEN 2-DIMENSIONAL ELECTRON GASES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Cerne, J.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Physical Review B, 1995)

Terahertz grid frequency doublers - Chiao, Jung-Chih; Markelz, Andrea; Li, Yongjun; Hacker, Jonathan; Crowe, Thomas; Allen, James; Rutledge, David (Proc. Sixth Intl. Symp. Space Terahertz Tech, 1995)

DC TRANSPORT IN INTENSE, INPLANE TERAHERTZ ELECTRIC-FIELDS IN AL(X)GA(1-X)AS HETEROSTRUCTURES AT 300-K - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Solid-State Electronics, 1994)
We report 300 K studies of the dependence of the in-plane, d.c. conductivity, sigma(d.c.) (E(omega)), of a quasi 2D electron gas on the amplitude E(omega) and frequency of intense, far-infrared fields (omega/2pi = 0.24-3.5 THz). We measure sigma(d.c.) (E(omega) parallel-to E(d.c.)), where E(d.c.) is a small sensing field, and observe a monotonic decrease in sigma(d.c.) with increasing E(omega). Although a simple scaling ansatz collapses the measured sigma(d.c.) (E(omega)) data onto a single curve for frequencies from 0.25-3.45 THz (at low to moderate scaled fields), the decrease in conductivity is substantially more rapid than expected from comparison to similar data taken by Masselink et al. [Solid-St. Electron. 31, 337 (1988)] at 35 GHz. We tentatively attribute this difference to effects of a high-frequency modulation in the electron temperature.

ENERGY RELAXATION AT THZ FREQUENCIES IN ALXGA1-XAS HETEROSTRUCTURES - Asmar, N. G.; Markelz, A. G.; Gwinn, E. G.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We report 4.2 K studies of the dependence of the in-plane, DC conductivity of a quasi 2D electron gas on the amplitude E(omega) of applied fields with frequencies from 0.25 THz to 3.5 THz. We analyse the dependence of sigma(DC) on E(omega) assuming that electron-optical phonon scattering dominates energy relaxation, that the absorbed power has a Drude form and that the electron distribution is thermal. This simple analysis is self-consistent: Arrhenius plots of the estimated energy loss rate have a slope near -homega(LO)BAR/k(B) for all frequencies, as expected for energy loss by optical phonon emission. We find that the effective energy relaxation time tau(epsilon) varies with the frequency of the applied field, from tau(epsilon) approximately 4 ps at 0.34 THz to tau(epsilon) approximately 0.3 ps at 3.45 THz. This may indicate a frequency-dependent form for the hot-phonon distribution.

Far-infrared harmonic generation from semiconductor heterostructures - Markelz, A.G.; Gwinn, E. G.; Sherwin, M. S.; Heyman, J. N.; Nguyen, C.; Kroemer, H. (SPIE Proceedings, 1994)

FAR-INFRARED SATURATION SPECTROSCOPY OF A SINGLE SQUARE-WELL - Craig, K.; Felix, C. L.; Heyman, J. N.; Markelz, A. G.; Sherwin, M. S.; Campman, K. L.; Hopkins, P. F.; Gossard, A. C. (Semiconductor Science and Technology, 1994)
We have performed saturation spectroscopy measurements of the lowest intersubband transition in a single 400 angstrom GaAs/Al0.3Ga0.7As modulation-doped square quantum well. We couple intense tunable far-infrared radiation from the Santa Barbara free electron laser into our sample using an edge-coupling technique and measure absorption as a function of frequency and intensity. Saturation and frequency shifts in the absorption line are clearly observed. We attribute the frequency shifts to reductions in the many-body depolarization shift. From our preliminary measurements, we estimate the intersubband relaxation time to be 600 ps to within a factor of three.

PROBING TERAHERTZ DYNAMICS IN SEMICONDUCTOR NANOSTRUCTURES WITH UCSB FREE-ELECTRON LASERS - Allen, S. J.; Craig, K.; Felix, C. L.; Guimaraes, P.; Heyman, J. N.; Kaminski, J. P.; Keay, B. J.; Markelz, A. G.; Ramian, G.; Scott, J. S.; Sherwin, M. S.; Campman, K. L.; et al. (Journal of Luminescence, 1994)
The UCSB free-electron lasers provide kilowatts of continuously tunable radiation from 120 GHz to 4.8 THz. They have the most impact on terahertz science and technology that require a tunable, high power source to explore non-linear dynamics or that sacrifice incident power to recover the linear response of systems with very small cross-section. We describe three experiments that demonstrate the utility of these lasers in experiments on the terahertz dynamics of semiconductor nanostructures: (i) terahertz dynamics of resonant tunneling diodes, (ii) saturation spectroscopy of quantum wells and (iii) photon-assisted tunneling in superlattices.

Far-infrared nonlinear response of electrons in semiconductor nanostructures - Sherwin, M. S.; Asmar, N. G.; Bewley, W. W.; Craig, K.; Felix, C. L.; Galdrikian, B.; Gwinn, E. G.; Markelz, A.G.; Gossard, A. C.; Hopkins, P. F.; Sundaram, M.; Birnir, B. (SPIE Proceedings, 1993)

Site-selective oxygen-isotope substitution in YBa2Cu3O7−δ - Morris, D. E.; Markelz, A. G.; Wei, J. Y. T.; Huitgren, C. T.; Nickel, J. H.; Hamilton, J. C.; McCarty, K. F. (Physical Review B, 1991)
We report selective substitution of oxygen-18 and oxygen-16 isotopes into the inequivalent oxygen lattice sites in YBa2Cu3O7−δ. The technique involves gas-phase diffusion and exploits the site dependence of diffusion rates. The CuO2-plane [O(2),O(3)] sites of YBa2Cu3O7−δ can be filled with 18O while the apical [O(4)] and CuO-chain sites [O(1)] contain 16O (the opposite distribution can also be made). The site-selective isotope occupation has been confirmed by Raman spectroscopy. Our method will permit experiments to determine the contributions of the different oxygen sites to the isotope effect, in order to locate the pairing interaction within the unit cell.

8 NEW HIGH-TEMPERATURE SUPERCONDUCTORS WITH THE 1-2-4 STRUCTURE - Morris, D. E.; Nickel, J. H.; Wei, J. Y. T.; Asmar, N. G.; Scott, J. S.; Scheven, U. M.; Hultgren, C. T.; Markelz, A. G.; Post, J. E.; Heaney, P. J.; Veblen, D. R.; Hazen, R. M. (Physical Review B, 1989)

OXYGEN CONCENTRATION EFFECT ON TC OF THE BI-CA-SR-CU-O SUPERCONDUCTOR - Morris, D. E.; Hultgren, C. T.; Markelz, A. M.; Wei, J. Y. T.; Asmar, N. G.; Nickel, J. H. (Physical Review B, 1989)